THE NOTION OF LINGUOCULTUREME AND ITS TYPES - Karina Kolesnikova (American Journals Publishing, 2023)
Linguoculturology, or cultural linguistics, just like any other scientific discipline, has its own terminology and a variety of aspects and trends. This article explores various trends of cultural linguistics and main notions of linguoculturology. However, the article mainly focuses on the definitions of linguocultureme as a basic unit of linguoculturology suggested by various researchers.
Keywords: Linguoculturology, cultural linguistics, linguocultural lexicography, linguocultureme.